SCORING OF PAIN PERCEPTION DURING PHACOEMULSIFICATION UNDER TOPICAL ANAESTHESIA - Khan, Mohammad Aamir; Aaqil, Bushra; Nazneen, Zainab; Faisal, Afsheen; Siddiqi, Zarrin; Latif, Riffat (Journal of Ayub Medical College Abbottabad, 2021)
Background: Topical anaesthesia is safe and inexpensive type of anaesthesia used during phacoemulsification as compared to local anaesthesia. The trend of conducting surgeries under topical anaesthesia is increasing globally. The objective of this study was to determine the perception of severity of pain during phacoemulsification using topical anaesthesia. Methods: This descriptive cross-sectional study was conducted at Jinnah International Hospital Abbottabad for a period of one year and included 196 patients of posterior subcapsular cataracts. Data was collected on a pretested structured questionnaire and analysed by SPSS version 20. Chi square test was used to find association between variables and p-value of equal or less than 0.05 was considered significant. Results: The mean age of the patients was 60.43±14.63 years. Out of 196 patients, 110 (56.1%) were males and 86 (43.9%) were females. During surgery pain score was 0 (no pain) in 149 (76%), 1 (mild) in 14 (7.1%), 2 (moderate) in 15 (7.7%) and 3 (severe) in 18 (9.2%) patients. Pain score was found to be significantly associated with gender (p=0.003) and age group (p=0.008). Conclusion: Phacoemulsification can be safely performed under topical anaesthesia in patients with posterior subcapsular cataracts with minimum intraoperative pain perception by the patients.